KAJIAN MODAL SOSIAL DALAM MENDUKUNG KETAHANAN PANGAN RUMAH TANGGA PETANI PADI DI DESA BODDIA KECAMATAN GALESONG KABUPATEN TAKALAR (Study Of Sosial Capital In Supporting Household Food Security Of Rice Farmers In Boddia Village, Galesong Sub-District, Takalar District) - AKBAR AKBAR; SUDARMIN SUDARMIN; RATNAWATI TAHIR (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
This study aimed to examine sosial capital in supporting rice farming household food security. The buying technique for informants was carried out by purposive sampling. Data collection by way of observation, interviews and documentation. The data analysis technique used is qualitative data analysis. The results of the study show that in realizing rice farmer household food security it is supported by the role of sosial capital as an adhesive in strengthening the role of farmers in society, including: (1) Trust in resilience in supporting rice farmer household food is an attitude of mutual trust and respect that is built between farmers and the community (2) Sosial networks in supporting rice farming household food security are sosial networks built on the basis of common interests, networks of power, kinship and kinship (3) Sosial norms in supporting rice farming household food security in the form of rules written and unwritten. Written sosial norms include the existence of written agreements related to planting schedules and types of seeds used in order to maintain production sustainability to fulfill household food agreements. The unwritten rules are in the form of a tradition called appa rappo (routine activities that are believed to make farming successful).